Genetic diversity in aromatic rice (Oryza sativa L.) - Anand, Anand Kumar (ORYZA-An International Journal of Rice, 2026)
Aromatic rice represents a valuable genetic resource, yet comprehensive diversity assessments of non-Basmati landraces from eastern India remain limited. In this study, 36 aromatic rice genotypes-including local landraces, released varieties, and mutants-were evaluated using 32 agro-morphological and quality traits alongside seven SSR markers to assess genetic variability and identify superior genotypes for breeding. Cluster analysis grouped the genotypes into seven distinct clusters, with Cluster I being the largest, while Clusters V, VI, and VII were monogenotypic, reflecting unique genetic backgrounds. Cluster III exhibited the highest intra-cluster variability, and the greatest inter-cluster distance was observed between Clusters VII and V, indicating potential for selecting genetically diverse parents. Cluster mean analysis revealed trait-specific superiority: Cluster II excelled in yield and nutritional traits, Cluster III in grain quality traits, and Cluster VII in both yield and iron content. SSR analysis indicated moderate polymorphism (PIC 0.204 - 0.405), with RM 5474 and RM 72 being highly informative. Unweighted pair group method with arithmetic mean (UPGMA) clustering further confirmed broad genetic diversity, highlighting the value of integrating phenotypic and molecular data for strategic hybridization and the development of improved aromatic rice cultivars.